La crise du socialisme réellement existant - Mandel, David (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
The Soviet Union and its East European glacis are experiencing their second major wave of crisis since the death of Stalin. But unlike the "de-stalinization" crisis of the second half of the 1950s, which was largely political and was overcome through a combination of repression and reform that left the system basically intact, the present crisis cannot be weathered so easily and threatens to usher in a period of political upheaval, as it has already in Poland and, to some extent, in Romania.On the most obvious level, the crisis manifests itself in the constant decline of the economic growth rate since the late 1950s, which has put an end to the slow but steady rise in living standards, the basis upon which the tacit post-Stalin accord between the bureaucracy and society was founded. The roots of this crisis are deeply structural, but structural reforms, in particular the introduction of the « regulated market mechanism », which appears to be the nly viable alternative open to the bureaucracy, will meet with strong opposition from important sectors of that elite, especially the provincial party bosses, and threaten to create a split in its ranks.At the same time, such a reform is politically unfeasible without important concessions to the working class in the direction of democratization or, at the least, the right to organize into independent trade unions to protect itself against management, whose powers would be greatly enhanced by the reform. But such concessions to the working class, as Poland shows, are perceived by the bureaucracy as a threat to its very existence. At the same time, the working class today is potentially a much more formidable political force than at any time since the civil war.The leadership is, therefore, in a dilemma. The 1980s are likely to see the explosive combination of a simultaneous crisis "as the top" and "at the bottom".